Analysis and management of traffic accident in Baghdad city - Z. Hadi, Inas (International Journal of Engineering and Technology, 2018)
Currently, the city of Baghdad in Iraq suffers from an increase in irrigated traffic accidents for several reasons; so, it is necessary to study the main factors and causes of traffic accidents in Baghdad and focus on the methods to mitigate them. A questionnaire was formulated based on the literature review to collect information on the perceived causes of traffic accidents in Baghdad. The questionnaire was distributed to the targeted professionals across Baghdad. After analyzing the collected data using the SPSS program, the results showed that the major cause of traffic accidents in the city was the driver as this factor accounted for most of the traffic accidents. The attitude of the passengers was observed as the least cause of traffic accident in the city while the vehicle factor is the most important among the main factors. Based on the research findings, a system has been proposed for controlling the most important causes of traffic accidents in Baghdad. The system was proposed to reduce traffic accidents through safety guidelines and the education of the drivers of the presence of danger to life. The use of industrial bumps that allow one-way traffic, as well as the use of speed indicators and cameras on highways to identify traffic offenders was also proposed. Finally, the imposition of sanctions and fines on those that violate traffic laws as well as the tests for alcohol and drug are equally suggested.Â Â